THE DESCRIPTIVE ANALYSIS OF TEACHER’S CLASSROOM MANAGEMENT IN TEACHING ENGLISH - Afore Tahir Harefa; Hasrat Sozanolo Harefa; Jevan Selamat Zega (Universitas Nias, 2022)
English teacher hold the most important role in teaching and learning activities. The teacher here as a facilitator to implement the learning process, where the teacher applies various strategies or learning methods that will be implemented in the teaching and learning process. One of the most important things in this case is about how a teacher manages a classroom as well as possible. So the purpose of this research is describe the teacher’s classroom management in teaching English, exactly at SMK Negeri 1 Lotu. To get data the researcher conducting observation and interview. Furthermore, the informants of the research were two english teacher who teach at the eleventh grade of SMK Negeri 1 Lotu. The data were gained from the teacher’s interview and observation reveal description of teacher’s classroom management in teaching English and the factors influenced the teacher’s classroom management in teaching English. To conduct this research, the researcher used stetement from garret. And after conducting observation and interview, the research findings were concluded: classroom management in teaching and learning process was divided into the physical design of classroom, rules and routines, relationship among students and teacher-students, engaging and motivation instruction, and the last is discipline. The five components were support the good classroom management in teaching English and influenced to the student’s achievement. Teachers required to be very creative in the classroom, and teacher teach student based on their style